Does Family Caregiver Burden Differ Between Elderly and Younger Caregivers in Supporting Dying Patients With Cancer? An Italian Study. (August 2020) - Spatuzzi, Roberta; Giulietti, Maria Velia; Ricciuti, Marcello; Merico, Fabiana; Romito, Francesca; Reggiardo, Giorgio; Birgolotti, Loredana; Fabbietti, Paolo; Raucci, Letizia; Rosati, Gerardo; Bilancia, Domenico; Vespa, Anna
Context: The aging of the world's population increasingly calls on older people to care for their cancer relatives. This scenario confronts clinicians involved with end-of-life care with an imposing challenge: elderly family caregivers could have a different perception of the burdens associated with assistance compared to their younger counterparts. Palliativists need to know what limits and resources of these new age categories of caregivers could be for a global management of dying patients with cancer and their family. Objectives: To evaluate the caregiver burden in family caregivers supporting dying patients with cancer in order to compare the differences between 2 different caregivers age groups (younger vs elderly population). Methods: This is a cross-sectional study. A total of 174 family caregivers of hospice patients were interviewed through the Caregiver Burden Inventory (CBI). The sample group was divided into 2 subgroups aged <65 (younger group) and ≥65 years old (elderly group). Results: Compared with younger caregivers, the elderly group reported significantly higher scores in the CBI–developmental subscale ( P = .009) confirmed by the generalized linear model (multivariate) evaluation that included possible predictors in the model. No further differences were found between the 2 age groups in the other CBI scores (time-dependent, physical, social, emotional, and overall score). Conclusion: Elderly caregivers are at high risk for experiencing developmental burden. This finding could prompt mental health professionals to pay greater attention to the value that assistance to the family member can have on their personal story and on that of the family or couple.